Haemodynamic-guided management of heart failure (GUIDE-HF): a randomised controlled trial. Issue 10304 (11th September 2021) - Lindenfeld, JoAnn; Zile, Michael R; Desai, Akshay S; Bhatt, Kunjan; Ducharme, Anique; Horstmanshof, Douglas; Krim, Selim R; Maisel, Alan; Mehra, Mandeep R; Paul, Sara; Sears, Samuel F; Sauer, Andrew J; et al.
Summary: Background: Previous studies have suggested that haemodynamic-guided management using an implantable pulmonary artery pressure monitor reduces heart failure hospitalisations in patients with moderately symptomatic (New York Heart Association [NYHA] functional class III) chronic heart failure and a hospitalisation in the past year, irrespective of ejection fraction. It is unclear if these benefits extend to patients with mild (NYHA functional class II) or severe (NYHA functional class IV) symptoms of heart failure or to patients with elevated natriuretic peptides without a recent heart failure hospitalisation. This trial was designed to evaluate whether haemodynamic-guided management using remote pulmonary artery pressure monitoring could reduce heart failure events and mortality in patients with heart failure across the spectrum of symptom severity (NYHA funational class II–IV), including those with elevated natriuretic peptides but without a recent heart failure hospitalisation. Methods: The randomised arm of the haemodynamic-GUIDEed management of Heart Failure (GUIDE-HF) trial was a multicentre, single-blind study at 118 centres in the USA and Canada. Following successful implantation of a pulmonary artery pressure monitor, patients with all ejection fractions, NYHA functional class II–IV chronic heart failure, and either a recent heart failure hospitalisation or elevated natriuretic peptides (based on a-priori thresholds) were randomly assigned (1:1) to either haemodynamic-guided heart failure management based on pulmonary artery pressure or a usual care control group. Patients were masked to their study group assignment. Investigators were aware of treatment assignment but did not have access to pulmonary artery pressure data for control patients. The primary endpoint was a composite of all-cause mortality and total heart failure events (heart failure hospitalisations and urgent heart failure hospital visits) at 12 months assessed in all randomly assigned patients. Safety was assessed in all patients. A pre-COVID-19 impact analysis for the primary and secondary outcomes was prespecified. This study is registered with ClinicalTrials.gov, NCT03387813 . Findings: Between March 15, 2018, and Dec 20, 2019, 1022 patients were enrolled, with 1000 patients implanted successfully, and follow-up was completed on Jan 8, 2021. There were 253 primary endpoint events (0·563 per patient-year) among 497 patients in the haemodynamic-guided management group (treatment group) and 289 (0·640 per patient-year) in 503 patients in the control group (hazard ratio [HR] 0·88, 95% CI 0·74–1·05; p=0·16). A prespecified COVID-19 sensitivity analysis using a time-dependent variable to compare events before COVID-19 and during the pandemic suggested a treatment interaction (pinteraction =0·11) due to a change in the primary endpoint event rate during the pandemic phase of the trial, warranting a pre-COVID-19 impact analysis. In the pre-COVID-19 impact analysis, there were 177 primary events (0·553 per patient-year) in the intervention group and 224 events (0·682 per patient-year) in the control group (HR 0·81, 95% CI 0·66–1·00; p=0·049). This difference in primary events almost disappeared during COVID-19, with a 21% decrease in the control group (0·536 per patient-year) relative to pre-COVID-19, virtually no change in the treatment group (0·597 per patient-year), and no difference between groups (HR 1·11, 95% CI 0·80–1·55; p=0·53). The cumulative incidence of heart failure events was not reduced by haemodynamic-guided management (0·85, 0·70–1·03; p=0·096) in the overall study analysis but was significantly decreased in the pre-COVID-19 impact analysis (0·76, 0·61–0·95; p=0·014). 1014 (99%) of 1022 patients had freedom from device or system-related complications. Interpretation: Haemodynamic-guided management of heart failure did not result in a lower composite endpoint rate of mortality and total heart failure events compared with the control group in the overall study analysis. However, a pre-COVID-19 impact analysis indicated a possible benefit of haemodynamic-guided management on the primary outcome in the pre-COVID-19 period, primarily driven by a lower heart failure hospitalisation rate compared with the control group. Funding: Abbott.